Diligence and persistence are Muhammad Aslam’s secret to excel twice - Shalfarina, Shahriman (UMPSA, 2024)
GAMBANG, 21 October 2023 - The success of obtaining a second-class diploma with a Cumulative Grade Point Average (CGPA) of 3.58 three years ago is the catalyst for Muhammad Aslam Zulkarnain, 23, to repeat the success while continuing his study at the bachelor’s level.